2016
DOI: 10.1161/circresaha.115.308077
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Ligand-Dependent Notch Signaling Activation Regulates Valve Primordium Formation and Morphogenesis

Abstract: During cardiac valve formation, Dll4-Notch1 signaling leads to epithelial-mesenchymal transition and cushion formation. Jag1-Notch1 signaling subsequently restrains Bmp-mediated valve mesenchyme proliferation by sustaining Hbegf-EGF receptor signaling. Our studies identify a mechanism of signaling cross talk during valve morphogenesis involved in the origin of congenital heart defects associated with reduced NOTCH function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
175
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(184 citation statements)
references
References 64 publications
9
175
0
Order By: Relevance
“…MFNG gene was also significantly downregulated in BAV-D compared to TAV-D ( P  < 0.00001, Supplementary Table 9). This was in line with the data published in mice25, supporting the regulatory role of MIB1 and MFNF for NOTCH pathway in BAV.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…MFNG gene was also significantly downregulated in BAV-D compared to TAV-D ( P  < 0.00001, Supplementary Table 9). This was in line with the data published in mice25, supporting the regulatory role of MIB1 and MFNF for NOTCH pathway in BAV.…”
Section: Resultssupporting
confidence: 92%
“…Fine tuning of NOTCH ligand-receptor interaction, either by ligand endocytosis activated by E3 ubiquitin ligase Mind Bomb ( MIB1) or by post translational modification of receptor via glycosyltransferase Manic Fringe ( MFNG ) in endocardium was reported to be required for the proper EndMT of cardiac cushion and formation of aortic valves in mice25. Using IHC, we showed a significantly higher expression of NOTCH3 and NOTCH1 intracellular domain (ICD), the ligands JAG1, JAG2, and DLL4 and a higher tendency for NOTCH4 expression ( P  = 0.0571) in intima-media of BAV-ND compared to TAV-ND (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although it is still unclear how to link discrete JAG1 mutations, which have variable effects on JAG1 trafficking and activity, to the range of cardiac defects observed in individuals with Alagille syndrome (Bauer et al, 2010), it has been shown that the development of several compartments of the heart is dependent on the balanced activities of Jag1 and Notch2. Ablation of Jag1 expression in the endocardium leads to outflow tract (OFT) defects, aortic valve hyperplasticity, tetralogy of Fallot and valve calcification, recapitulating the spectrum of cardiac pathologies often present in Alagille syndrome MacGrogan et al, 2016). These phenotypes are, at least partially, linked to cardiac neural crest (CNC) cells, a highly migratory cell population that originates from the neural plate border .…”
Section: Notch2 and Jag1 Function In Heart Developmentmentioning
confidence: 99%
“…Deletion of endothelial-derived Jag1 in a subset of endothelial cells that do not undergo EMT leads to thickened arterial valves, BAV, and VSD that was shown to be mediated by endothelial-Notch1. Transcriptome analysis revealed increased BMP signaling and mesenchymal cell proliferation, and also led to the identification of a new Notch effector, Heparin binding epidermal growth factor (EGF) like growth factor, required to suppress mesenchymal cell proliferation and potentially play a role in embryonic valve hypertrophy [29]. …”
Section: Molecular Pathways For Aortic Valve Developmentmentioning
confidence: 99%